Aplikasi Teknologi Bakteri Dalam Pekerjaan Restorasi Sungai Xuxi, Kota Wuxi, China - Doddi Yudianto; Xie Yuebo (JURNAL TEKNIK HIDRAULIK, 2010)
Considering previous successful applications of biological treatment in several restoration works in China,this study is aimed to describe the complete processes and results derived from the application of bacterialtechnology in restoring urban river. Here the Xuxi River in Wuxi City was selected as an example of casestudy.Basedontheresultsobtained, itisfoundthat this bacterial technologyisabletoprovidebroaderviewsof river restoration workfor urban area. Besides it results better water quality,the water is now clearer andcontains aquatic life. Although a considerable increase of concentration of total phosphorus, total nitrogen,and ammonium nitrogen may have enhanced to Algae problem during the treatment, but the final resultsshow good achievement. Detail laboratory tests and mathematical model development are necessary tooptimize the implementation.